High-Resolution SD-OCT and EDI-OCT in the Evaluation and Management of Multifocal Serpigenoed Choroditis - Abo Taleb Eman; P. Nagpal Manish; S. Mehrotra Navneet (Journal of Ophthalmic Science, 2019)
Purpose To describe spectral domain optical coherence tomography (SD-OCT) and enhanced depth image OCT (EDI-OCT) findings of multifocal serpiginoid choroditis (MSC) , including affected layer of retinal involvement, changes at the vitreoretinal interface, and response to therapy. Methods A retrospective review of 20 eyes (14 patients) with MSC. Each patient underwent a complete ophthalmologic examination, fundus photography, fundus autoflorecence (FAF) and OCT imaging of the affected retina at the initial visit and on each follow-up. Results In acute stage, SD-OCT showed hyperreflective areas involving the outer retinal layers which include retinal pigment epithelium (RPE), photoreceptor outer segment tips (POST), inner segment–outer segment (IS/OS) junction, external limiting membrane (ELM), and outer nuclear layer (ONL) with choroidal and intraretinal layer cells infiltrate. EDI-OCT showed increase choroidal thickness. As the lesions began to heal, irregular, knobby elevations of outer retinal layers appeared (RPE, POST, IS/OS junction, and ELM could not be distinguished) with significant decrease in choroidal and intraretinal cells. On complete healing, loss of RPE, POST, IS/OS junction, and ELM in SD-OCT scan and absent of the choroidal and intraretinal cells and continous hyperreflactivity of the choroid (increased penetrance). Conclusion SD-OCT and EDI-OCT provides high-resolution detail regarding ultrastructural changes in vitreoretinal interface, outer retina and choroid during the course of the lesion. Serial SD-OCT and EDI-OCT also provides further insight into response to therapy by observing choroidal and intraretinal cells.
Keywords: Serpiginous multifocal choroiditis